Respuesta :

Answer:

x = 2.

Step-by-step explanation:

Solve for x:

0.3 (4 - x) = x - 1.4

Expand out terms of the left hand side:

1.2 - 0.3 x = x - 1.4

Subtract x from both sides:

1.2 + (-0.3 x - x) = (x - x) - 1.4

-0.3 x - x = -1.3 x:

-1.3 x + 1.2 = (x - x) - 1.4

x - x = 0:

1.2 - 1.3 x = -1.4

Subtract 1.2` from both sides:

(1.2 - 1.2) - 1.3 x = -1.2 - 1.4

1.2 - 1.2 = 0:

-1.3 x = -1.2 - 1.4

-1.2 - 1.4 = -2.6:

-1.3 x = -2.6

Divide both sides of -1.3 x = -2.6 by -1.3:

(-1.3 x)/(-1.3) = (-2.6)/(-1.3)

(-1.3)/(-1.3) = 1:

x = (-2.6)/(-1.3)

(-2.6)/(-1.3) = 2.:

Answer:  x = 2.

ACCESS MORE